Cocaine falls into oblivion during volitional initiation of choice trials. (4th October 2022) - Vandaele, Youna; Augier, Eric; Vouillac‐Mendoza, Caroline; Ahmed, Serge H.
Abstract: When facing a choice, most animals quit drugs in favour of a variety of nondrug alternatives. We recently found, rather unexpectedly, that choice of the nondrug alternative is in fact inflexible and habitual. One possible contributing factor to habitual choice is the intermittency and uncontrollability of choice trials in previous studies. Here, we asked whether and to what extent volitional control over the occurrence of choice trials could change animals' preference by preventing habitual choice. To do so, rats were trained to nosepoke in a hole to trigger the presentation of two operant levers: one associated with cocaine, the other with saccharin. Rats were then free to choose among the two levers to obtain the corresponding reward, after which both levers retracted until rats self‐initiated the next choice trial. Overall, we found that volitional control over choice trials did not change preference. Most rats preferred saccharin over cocaine and selected this option almost exclusively. Intriguingly, after repeated choice and consumption of saccharin, rats transiently lost interest in this option (i.e., due to sensory‐specific satiety), but they did not switch to cocaine, preferring instead to pause during long periods of time before reinitiating a choice trial for saccharin. This finding suggests that during volitional initiation of a choice trial, rats fail to consider cocaine as an option. We discuss a possible associative mechanism to explain this perplexing behaviour. Abstract : Rats were offered volitional control over the occurrence of choice trials between cocaine and sweet water. To do so, they were trained to nosepoke in a hole to trigger the presentation of these two options. Overall, volitional control over choice trials had no effect on preference.